Cautín Island Urban Park, Temuco, Chile, 2023. Hydro-ecological infrastructure for urban resilience - Osvaldo Moreno (ARQ, 2023)
Located between two water courses, the Isla Cautín urban park serves as hydroecological infrastructure and public space. A sequence of floodable meadows, canals, ponds, and wetlands retains and infiltrates urban runoff, reducing the risk of flooding in a scenario where its frequency is projected to increase.